How to Make the Passions Active: Spinoza and R.G. Collingwood. (July 2019) - Douglas, Alexander
Abstract: Most early modern philosophers held that our emotions are always passions : to experience an emotion is to undergo something rather than to do something. Spinoza is different; he holds that our emotions – what he calls our 'affects' – can be actions rather than passions. Moreover, we can convert a passive affect into an active one simply by forming a clear and distinct idea of it. This theory is difficult to understand. I defend the interpretation R.G. Collingwood gives of it in his book, The Principles of Art . An affect, it turns out, is passive when it is ambiguous whether we or somebody else is the subject of the affect. An affect is active when we fully accept the affect as our own. Here, I outline Collingwood's interpretation and then develop it further.